The effect of immunoregulatory bacteria on the transcriptional activity of foxp3 and roryt genes in the gut-associated lymphoid tissue with salmonella-induced inflammation in the presence of vancomycin and ваcteroides fragilis - Bukina, Yu. V.; Thyhonovska, M.; Koval, M.; Marushchak, M.; Krynytska, I.; Kamyshnyi, A.; Букіна, Юлія Вячеславівна; Тихоновська, Марина Анатоліївна; Коваль, М.; Марущак, М.; Криницька, І.; Камишний, Олександр Михайлович (My University, 2020)
Intestinal microbiota is involved in the development and maintenance of immune homeosta-sis. This study was conducted to investigate the levels of key immunoregulatory bacteria in the intestinal wall-associated microflora and its effect on the transcriptional activity of the Foxp3 and RORyt genes in the gut-associated lymphoid tissue (GALT) of rats with Salmonella-induced inflammation, both untreated and treated with vancomycin and Bacteroides fragilis.Materials and Methods: To determine the levels of immunoregulatory bacteria in GALT of rats Q-PCR was used to identify them by species-specific 16S rDNA genes. Transcriptional activity of Foxp3 and RORyt genes was determined using Q-PCR with reverse transcription. Results: In animals treated with both vancomycin and Salmonella, the levels of segmented filamentous bacteria (SFB) in-creased while Akkermansia muciniphila and Faecalibacterium prausnitzii decreased. In rats that received pretreatment with vancomycin and then were infected with S. Enteritidis and S. Typhimurium, the levels of SFB increased, and the number of Bacteroides-Prevotela group, A. muciniphila, Clostridium spp. clusters XIV, IV, and F. prausnitzii significantly decreased, decreasing Foxp3 and increasing Rorγt mRNA expression. Administration of B. fragilis to animals treated with S. Enteriti-dis or S. Typhimurium and pre-treated with vancomycin caused a decrease in SFB and Rorγt mRNA levels and conversely, increased the numbers of the Bacteroides-Prevotela group, Clostridium spp. clusters XIV, IV, A. muciniphila, F. prausnitziiand Foxp3 gene expression in GALT.Conclusion: Our results suggest that the commensal microorganism B. fragilis may provide a protective role against the development of experimental colitis, which has to be taken into consideration for further clarification of the effective thera-peutic strategy of inflammatory bowel diseases, irritable bowel syndrome and necrotising colitis.
Keywords: Salmonella; Vancomycin; Bacteroids; Immunoregulation; Genes expression